Terbentuknya Ruang Komunal dalam Aktivitas Accidental di Dukuh Krajan, Kromengan,Kabupaten Malang - Sri Winarni; Galih Widjil Pangarsa; Antariksa Antariksa; Lisa Dwi Wulandari (RUAS (Review of Urbanism and Architectural Studies), 2013)
Dukuh Krajan at Kromengan village is settlement in Malang. It located on the slopes of Kawi mountain, at the south side. The majority of societies are farmer. In Dukuh Krajan, traditional, social and cultural values were still exist and maintained. The recent phenomenon showed that physical development in there had depleted togetherness and mutual cooperation (gotong-royong) in social life of the society. It influenced spatial changing especially communal space. Case of this research were taken in accidental activities of marriage and death ceremonies. Method used was qualitative research method with rasionalistic approach. The data collected by observations and interviews with local leaders. Semipublic, semiprivate, and private space at wedding and death ceremony (tahlil) would change its function to serve as communal spaces. These changes were influenced by several factors: kinship, family, time, activities and actors. Community of Dukuh Krajan kept togetherness and mutual cooperation by mutual respect of one another and sense of belonging and appreciation to its environment.Keywords: communal spaces, accidental activity, rural settlement